COVID-19 Vaccine Uptake and Intent Among Emergency Healthcare Workers: A Cross-Sectional Survey. Issue 10 (October 2021) - Pacella-LaBarbara, Maria L.; Park, Yunseo Linda; Patterson, P. Daniel; Doshi, Ankur; Guyette, Maria Koenig; Wong, Ambrose H.; Chang, Bernard P.; Suffoletto, Brian P.
Abstract : Objective: Vaccine hesitancy limits population protection from SARS-CoV (coronavirus disease [COVID-19]). Vaccine hesitancy among healthcare workers (HCW) could put patients and coworkers at risk. Methods: We surveyed 475 emergency department and emergency medical service workers from January to February 2021 to determine vaccine intent/uptake, perceived COVID-19 vulnerability, and factors associated with vaccine intent/uptake. Results: Although 79% of HCWs received or had plans to receive the COVID-19 vaccine, 21% had no intent/were unvaccinated; intent/uptake was lower among females (odds ratio [OR] = 0.34) and those with a history of COVID-19 infection (OR = 0.55), and higher among those with advanced degrees (OR = 3.53) and high perceived COVID-19 vulnerability (OR = 1.99). Conclusions: This study provides a timely assessment of vaccination status among frontline HCWs and highlights subgroups who may be at high risk of exposure and transmission.